Evaluation of the vitamin D and biomedical statuses of young children with β-thalassemia major at a single center in southern China - Uet Yu; Li Chen; Xiaodong Wang; Xiaoling Zhang; Yue Li; Feiqiu Wen; Sixi Liu (BMC, 2019)
Abstract Background In young children, β-thalassemia major (β-TM) is associated with potentially severe clinical characteristics, including poor growth, feeding difficulties, hepatosplenomegaly, bone metabolic disorders, and skeletal abnormalities. Methods In this study, we reviewed the demographic and clinical characteristics (e.g., age, sex, duration of blood transfusion and chelating therapy, and vitamin supplementation) and serum biomarker levels (e.g., iron accumulation, bone metabolism, liver, kidney, and thyroid function markers) of 32 patients that received regular blood transfusion at a single center in southern China with the aim of stratifying the risk of severe complications such as osteopenia, endocrinopathies, and multi-organ failures. Results Although all patients exhibited moderately to strongly elevated serum ferritin levels, this biomarker was significantly higher in children older than ≥5 years, compared to younger children (*p < 0.05, 1512 ± 192.6 vs. 2337 ± 299.8 ng/ml, Mann-Whitney U test). Older children had a significantly lower 25-hydroxy vitamin D3 (25(OH)D3) level, compared to younger children (**p < 0.01, 34.25 ± 11.06 vs. 23.05 ± 9.95 ng/ml, Mann-Whitney U test). No age-related differences were observed in serum calcium, phosphorus, and PTH levels. Regarding liver function, the serum alanine aminotransferase (ALT) level was significantly increased in children older than ≥5 years, compared to younger children (*p < 0.05, 19.17 ± 2.44 vs. 43.45 ± 9.82I U/ml, Mann-Whitney U test). However, no age-related differences were observed in the serum levels of other liver or kidney and thyroid biomarkers. Conclusions Our results suggest that in older children, hepatic iron overload may be associated with a low serum concentration of 25(OH)D3, an indicator of vitamin D deficiency and altered bone metabolism. Iron accumulation may also be associated with a higher concentration of ALT, a sensitive marker of liver malfunction. These findings may provide important clinical indications of the need for intervention to prevent severe complications in children with β thalassemia.